Beneficial effects of Aloe ferox on lipid profile, blood pressure, and glycemic control in obese persons: A CONSORT-clinical study. Issue 50 (17th December 2021) - Gherbon, Adriana; Frandes, Mirela; Timar, Romulus; Nicula, Marioara
Abstract: Background: Aloe ferox is one of the most widely used medicinal plants today, with the most intense detoxifying action of all aloe species, being used in the treatment of various diseases, including obesity. Our study aimed to assess the efficacy of Aloe ferox in obesity treatment. Methods: The study sample included 20 Romanian persons with obesity treated with diet and Aloe ferox based supplements, and 20 Romanian matched controls treated with diet and a placebo. The treatment included 2 capsules/day ( Aloe ferox 460 mg) for 2 weeks, followed by a 2-week break, repeated 3 times. The blood pressure (systolic and diastolic) and anthropometric parameters, such as body mass index (BMI), total cholesterol, and abdominal circumference, as well as the biochemical parameters, fasting blood glucose (FBG), uric acid, and lipid profile was evaluated at baseline and after 3 months. Results: After 3 months of Aloe ferox administration, significant differences between the study group and the control group were observed regarding BMI ( P  = .03), total cholesterol ( P  = .032), low-density lipoprotein cholesterol (LDLc) ( P  = .01) and FBG ( P  = .018). Also, between the initial clinical, anthropometric, and biological parameters and those after the administration of Aloe ferox in the study group, we obtained significant differences regarding BMI ( P  = .002), LDLc ( P  = .039), fasting glycemia ( P  < .001) and diastolic blood pressure ( P  = .006). Conclusions: The administration of Aloe ferox to obese patients has been shown to achieve a significant reduction in body weight, BMI, LDLc, and FBG. These effects may be due to the laxative and detoxifying action of Aloe ferox components. As it can only be administered for limited periods due to side effects, further experimental and human studies of the efficacy of this plant in the treatment of obesity are needed.